THE ROLE OF THE FAMILY IN SUPPORTING THE EDUCATION OF CHILDREN WITH SPECIAL NEEDS IN THE HOME AND SCHOOL ENVIRONMENT - Siti Latifah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study aims to describe the role of the family in supporting the education of children with special needs (ABK) in the home and school environment. Using a qualitative approach with a case study method, data was obtained through in-depth interviews, observations, and documentation of several families with children with special needs in inclusive schools. The results of the study show that families provide support in the form of learning assistance, emotional strengthening, routine creation, and management of a conducive learning environment at home. In addition, parental involvement in school activities such as teacher consultations, parent meetings, and the preparation of individualized education programs also strengthen the success of children's learning processes. However, the study also identified a number of barriers faced by families, including limited time, knowledge, costs, and social pressures from the environment. These findings confirm that the role of the family is very important and multidimensional in the education of children and children. Therefore, synergy between families, schools, and communities is needed to create an inclusive and sustainable education system. This study provides recommendations for educational institutions and policy makers to strengthen the role of families in assisting children with special needs.